Hip Arthroscopic Surgery in the Context of Femoroacetabular Impingement Syndrome, Labral Tear, and Acetabular Overcoverage: Minimum 5-Year Outcomes With a Subanalysis Against Patients Without Overcoverage. Issue 1 (January 2021) - Maldonado, David R.; Diulus, Samantha C.; Shapira, Jacob; Rosinsky, Philip J.; Kyin, Cynthia; Ankem, Hari K.; Lall, Ajay C.; Domb, Benjamin G.
Background: Improvement in patient-reported outcomes (PROs) has been reported in the short term after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and labral tear in the setting of acetabular overcoverage. Yet, there is a paucity of information in the literature on midterm PROs. Purpose: To (1) report minimum 5-year PROs in patients who underwent primary hip arthroscopy for FAIS and acetabular labral tears in the context of acetabular overcoverage and (2) compare outcomes with those of a propensity-matched control group without acetabular overcoverage. Study Design: Cohort study; Level of evidence, 3. Methods: Data were prospectively collected and retrospectively analyzed on all patients who underwent hip arthroscopy for FAIS and labral tears between February 2008 and November 2013. Inclusion criteria were lateral center-edge angle >40° and minimum 5-year follow-up for the modified Harris Hip Score (mHHS), Nonarthritic Hip Score (NAHS), and the Hip Outcome Score–Sports-Specific Subscale (HOS-SSS). Exclusion criteria were previous ipsilateral hip surgery or conditions, active workers' compensation claims, or lack of minimum 5-year outcomes. A 1:1 propensity-matched comparison was made between the study group and a control group without acetabular overcoverage (lateral center-edge angle, 25°-40°) based on age at surgery, sex, body mass index, Tönnis grade, laterality, and follow-up time. The minimal clinically important difference (MCID) was calculated for the mHHS, HOS-SSS, and NAHS. Secondary surgical procedures were recorded. Results: A total of 54 patients satisfied the inclusion criteria for the study group, of whom 45 (83.3%; 45 hips) had a minimum 5-year follow-up and were matched without differences in age at surgery, sex, body mass index, or follow-up time. The study and control groups demonstrated significant and comparable improvements for the mHHS (mean ± SD Δ, 24.06 ± 24.19 vs 26.33 ± 17.27; P = .625), NAHS (Δ, 31.22 ± 25.31 vs 27.15 ± 17.61; P = .399), and HOS-SSS (Δ, 33.16 ± 34.73 vs 34.75 ± 26.15; P = .557). The rates for achieving the MCID were similar for the study and control groups for the mHHS (76.7% vs 84.2%; P = .399), HOS-SSS (79.1% vs 75.8%; P = .731), and NAHS (81.4% vs 84.2%; P = .738). Need for revision surgery was similar ( P = .748). A lower conversion rate to total hip arthroplasty was reported for the study than for the control group (2.2% vs 15.6%; P = .026). Conclusion: In the context of FAIS, labral tears, and acetabular overcoverage, patients who underwent hip arthroscopy reported significant improvement in several PROs at minimum 5-year follow-up. Moreover, outcomes were comparable with those of a propensity-matched control group without acetabular overcoverage. Furthermore, the rate of achieving the MCID for the mHHS, HOS-SSS, and NAHS was similar between these groups.